ChemInform Abstract: Synthesis, Crystal Structure and Properties of Mg3B36Si9C and Related Rare Earth Compounds RE3‐xB36Si9C (RE: Y, Gd—Lu). Issue 36 (15th August 2013) - Ludwig, Thilo; Pediaditakis, Alexis; Sagawe, Vanessa; Hillebrecht, Harald
Abstract Black single crystals of Mg3B36Si9C are synthesized from the elements at 1600 °C (h‐BN crucibles welded in Ta ampules, 40 h).